2007
DOI: 10.1136/gut.2007.134213
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic tri-modal imaging for detection of early neoplasia in Barrett's oesophagus: a multi-centre feasibility study using high-resolution endoscopy, autofluorescence imaging and narrow band imaging incorporated in one endoscopy system

Abstract: In this international multi-centre study, the addition of AFI to HRE increased the detection of both the number of patients and the number of lesions with early neoplasia in patients with Barrett's oesophagus. The false positive rate of AFI was reduced after detailed inspection with NBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(176 citation statements)
references
References 23 publications
5
160
1
10
Order By: Relevance
“…При этом электронная система искусственно окраши-вает аутофлюоресцентное изображение нормальной ткани в зе-леный цвет, очаги неоплазии и рака -в пурпурный цвет, синий цвет или в виде темного пятна. Полученные изображения сумми-руются и отображаются на экране [39].…”
Section: аутофлюоресцентная бронхоскопияunclassified
“…При этом электронная система искусственно окраши-вает аутофлюоресцентное изображение нормальной ткани в зе-леный цвет, очаги неоплазии и рака -в пурпурный цвет, синий цвет или в виде темного пятна. Полученные изображения сумми-руются и отображаются на экране [39].…”
Section: аутофлюоресцентная бронхоскопияunclassified
“…A multicenter study demonstrated a significant reduction of false positives when integrating NBI and AfI to a HRE in a trimodal prototype (70).…”
Section: Autofluorescencementioning
confidence: 99%
“…Standard high-resolution white light endoscopy only allows the detection of macroscopically obvious abnormalities. The adoption of narrow band imaging [43,44] , autofluorescence imaging [44] chromoendoscopy and virtual chromoendoscopy [45,46] could significantly improve the detection of dysplasia. A promising technique is that of confocal laser endomicroscopy (CLE), which allows in vivo visualisation of the mucosal histology.…”
Section: Lgd: Surveillance Alone?mentioning
confidence: 99%